The snow globe - Roberts, Sheila, 1951- (St. Martin's Press, 2010)
On a blustery afternoon, Kylie Gray wanders into an antique shop and buys an enchanting snow globe. "There's a story behind that snow globe," the antique dealer tells her. The original owner, he explains, was a German toymaker who lost his wife and son right before Christmas. When the grieving widower received the handcrafted snow globe as a Christmas gift, he saw the image of a beautiful woman beneath the glass<U+2014>a woman who would come into his life, mend his broken heart and bring him back to the world of the living. For years, the snow globe has passed from generation to generation, somehow always landing in the hands of a person in special need of a Christmas miracle. Kiley could use a miracle herself. This year, all she wants for Christmas is someone to love. A hopeful shake leads her on an adventure that makes a believer out of her. When Kylie shares the story of the snow globe with her best friends<U+2014>two women with problems of their own<U+2014>they don't believe it. But they're about to discover that at Christmastime, sometimes the impossible becomes possible and miracles really do come true.